FEATURES OF THE COURSE OF COVID-19 IN DISEASES OF THE CARDIOVASCULAR SYSTEM (World Bulletin of Public Health, 2023)
The pandemic of novel coronavirus infection (COVID-19), spread by the SARSCoV-2 virus, is a challenge to health systems worldwide. The most frequent manifestation of COVID-19 is involvement of the respiratory system. However, the disease is characterised by highly active inflammation and thrombotic complications leading to multi-organ lesions. Management of COVID-19 involves not only the treatment of pneumonia and respiratory failure, but also the timely recognition and treatment of other target organ damage